Goat health and sustainable goat farming in eastern India - Kumari, Rashmi Rekha; Kumar, Pankaj; Tripathi, Manoj Kumar; Singh, Jaspreet (Indian Farming, 2023)
Goat farming has been a source of income for the resource-poor. It has vast potential as a startup and entrepreneurship with value addition and organic milk. The importance of goat milk has caught attention with recent outbreaks of dengue fever and the COVID-19 pandemic. Goat is a hardy animal with minimal investment for taking up goatary. Understanding health and management problems and their remedial measures can further sustain goat farming and enhance income. Farmers should be aware of important health management related to diseases like PPR (Peste des petits ruminants), ORF (Contagious ecthyma), endoparasitism, urinary stones, etc. commonly challenged in goat herds. However, these challenges can be easily overcome if suitable measures and understanding are attained.